Implementation of a district management system in the Lower Rio Grande Valley of Texas - Fipps, Guy, author; Pope, Craig, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1998)
The Lower Rio Grande Valley of Texas is undergoing rapid population growth and industrial development. No additional water rights are available in the lower Rio Grande River Basin, and future development will depend on water transfers from agriculture. The potential for saving water in irrigation districts is being studied as part of a regional water resources planning project. An Irrigation District Management System (DMS) is under development to aid in this analysis. The DMS is built upon GIS-based maps and databases for organizing and displaying district information on water accounts, fields, and distribution systems. Various other components are being linked to the DMS or are under development to enhance its capabilities, including a crop growth and irrigation scheduling model for determining water use under various water supply scenarios, and a routing model for determining the ability of the distribution systems to deliver the volumes of water needed for each scenario. The implementation of the DMS in the Valley and its use in regional water planning is described.
USCID 14th technical conference
District management system
Not digitized by CSUL Digital Services.
Presented at Contemporary challenges for irrigation and drainage: proceedings from the USCID 14th technical conference on irrigation, drainage and flood control held on June 3-6, 1998 in Phoenix, Arizona.